Stochastic methods in subsurface contaminant hydrology - Govindaraju, Rao S. (ASCE Press, 2002)
"Stochastic Methods in Subsurface Contaminant Hydrology is a compilation of existing methodologies and emerging techniques that are available for performing stochastic analysis of contaminant transport through porous media. Analytical tools, such as perturbation methods, spectral analysis, spatial and temporal moments, cumulant expansions, streamtube approaches, decomposition methods, and Kalman filtering, are covered in various chapters of the book. Concepts of reactive and nonreactive transport, dilution, anomalous dispersion, and others are illustrated through examples from field and laboratory experiments and from simulation exercises."